Dinamika Hukum Perkawinan Perspektif Hukum Keluarga Islam: Studi Kasus Jasa Nikah Siri Online Di Parepare - Anwar, Wirani Aisiyah; Aris, Aris; Mutmainah, Iin; Jesika, Jesika; Al-Magfira Salsabila, Nurul (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
This study aims to examine the factors that cause the emergence of online nikah siri online and its impact from the perspective of maṣlaḥah (benefit) and maḍarrah (harm) in Islamic family law. Using a field-based qualitative research method, data is obtained through interviews and documentation, then analysed through interviews and documentation, then analysed systematically. The results show that this service ignores the legal provisions in Law Number 1 Year 1974 and risks harming women and children, especially in the rights to maintenance, inheritance, and post-divorce legal protection. The implications of these findings emphasise the need for strengthened regulation and supervision of online nikah siri, as well as increasing public awareness of the importance of marriage registration. of marriage registration. In addition, a legal policy reform that is not only repressive but also preventive is recommended, legal policy reforms that are not only repressive but also preventive, such as the simplification of marriage registration proceduresprocedures for marriage registration. Thus, this research contributes to recommendations for the government, law enforcement and religious institutions to improve legal protection for families in Indonesia.